The mediating role of body surface area-adjusted basal metabolic rate: effects of low muscle mass and central obesity on cognitive impairment in Chinese patients with type 2 diabetes mellitus - Zhai, Ya-Jie; Li, Fang; Lin, Chen-Ying; Wu, Fan; Qiu, Hui-Na; Li, Jing-Bo; Lin, Jing-Na (Frontiers in Endocrinology, 2025)
BackgroundThis study investigates the relationship between basal metabolic rate (BMR), body composition, obesity indices, and cognitive impairment (CI) in middle-aged and older type 2 diabetes mellitus (T2DM) patients, assessing their potential role in CI screening.MethodsA cross-sectional study included 1243 T2DM patients over 45 years old. CI was assessed using the Montreal Cognitive Assessment. BMR and body composition indices were measured through bioelectrical impedance analysis. The associations and predictions related to CI were explored using multivariable-adjusted logistic regression, restricted cubic spline (RCS) models, and receiver operating characteristic (ROC) curve analyses. Mediation analysis explored the role of BMR adjusted by body surface area (BMR/BSA) in CI risk.ResultsPatients with CI showed significantly lower BMR, BMR adjusted for height squared (BMR/Height²), BMR/BSA, appendicular skeletal muscle mass (ASM), and fat-free mass (FFM), alongside higher waist circumference (WC) and percentage of body fat. Logistic regression showed that participants in the fourth quartile of BMR, BMR/Height2, and BMR/BSA had approximately a 54% reduced risk of CI (odds ratio range 0.457 to 0.463). RCS analysis indicated a linear decrease in CI risk with increasing BMR metrics. ROC analysis indicated high predictive efficacy for CI with combined indicators, particularly BMR and FFM (area under the curve 0.645). Mediation analysis suggested that BMR/BSA played a significant mediating role in WC, ASM and FFM on CI risk, with a mediation proportion ranging from 45.73% to 50.87%.ConclusionLow energy expenditure assessed by BMR/BSA is an independent risk factor for increased CI risk in middle-aged and elderly T2DM patients. Central obesity, low muscle mass, and low energy expenditure significantly elevate CI risk in this population.